Genomic Research in Reproduction and Biobanking: An Analysis of International Legal Approaches - Kosilkin, Sergey Vyacheslavovich; Kubyshkin, Aleksey Viktorovich; Moskovkina, Elizaveta Kirillovna; Nekoteneva, Maria Vladimirovna; Tyumentsev, Vladislav Olegovich (International Journal of Criminology and Sociology, 2022)
The article examines the regulatory issues of genomic research in human reproduction and biobanking. The approaches to legal regulation at the level of international law, integration organizations, and individual states are analyzed. Based on the analysis, proposals for legal regulation are formulated. Regarding the legal regulation of genomic research in the field of biobanking, the article discusses the issue of the legal standing of biobanks, approaches to the legal regulation of biobanks in various countries, and formulates proposals for the commercial use of the results of genomic research in biobanking. The article also provides an overview of some judicial decisions that had a certain impact on forming legal regulation of genomic research in the field of biobanking and human reproduction.